Advances in the Neuro-Rehabilitation of Parkinson’s Disease: Insights from a Personalized Multidisciplinary Innovative Pathway - Maria Grazia Maggio; Mirjam Bonanno; Alfredo Manuli; Rosaria De Luca; Giuseppe Di Lorenzo; Angelo Quartarone; Rocco Salvatore Calabrò (Biomedicines)
Background/Objectives: Parkinson’s disease (PD) is a progressive neurodegenerative disorder that requires comprehensive and personalized rehabilitation. This retrospective study focused primarily on the usability and patient acceptability of the innovative pathway. In addition, the secondary objective was to evaluate the effectiveness of a personalized and multidisciplinary rehabilitation pathway on cognitive function, especially executive functions. Methods: We conducted a retrospective study on 80 patients with PD (Hoehn and Yahr scores 1–3). Patients were divided into an experimental group (EG), which received the innovative pathway, and a control group (CG), which received traditional therapy. The rehabilitation program included three phases: initial outpatient assessment, a two-month inpatient program, and a telerehabilitation phase in a day hospital (DH) or home environment. Interventions combined traditional therapies with treatments based on robotic and virtual reality. Cognitive assessments (Mini Mental State Examination—MMSE—and frontal assessment battery—FAB), mood (Hamilton Rating Scale—Depression—HRS-D), anxiety (HRS-Anxiety—HRS-A), and goals achievement (GAS) were the primary outcome measures. Results: At baseline, there were no significant differences between the groups in terms of age, gender, education, or test scores. After rehabilitation, EG showed significant improvements in all measures (p < 0.001), particularly in cognitive tests and goal achievement. CG improved in GAS (p < 0.001) and mood (HRS-D, p = 0.0012), but less than EG. No significant changes were observed in the MMSE of CG (p = 0.23) or FAB (p = 0.003). Conclusions: This study highlights the high usability and acceptability of VR and robotics in PD rehabilitation, contributing to improved adherence and patient engagement. The experimental group showed greater cognitive benefits, particularly in executive functions. These results are in line with the existing literature on personalized technology-based rehabilitation strategies for PD.